Using SnO2 QDs and CsMBr3 (M = Sn, Bi, Cu) QDs as Charge‐Transporting Materials for 10.6%‐Efficiency All‐Inorganic CsPbBr3 Perovskite Solar Cells with an Ultrahigh Open‐Circuit Voltage of 1.610 V (Solar RRL 3∕2019). Issue 3 (7th March 2019) - Zhao, Yuanyuan; Duan, Jialong; Yuan, Haiwen; Wang, Yudi; Yang, Xiya; He, Benlin; Tang, Qunwei
Abstract : In article no.1800284, Qunwei Tang and co‐workers apply SnO2 QDs and CsMBr3 (M = Sn, Bi, Cu) QDs as electron transporting and hole transporting materials for all‐inorganic CsPbBr3 PSCs, respectively. Owing to the high optical transmittance and electron mobility of the SnO2 QDs electron transport layer as well as the hole extraction of CsMBr3 QD hole transport layer, the device achieves a champion power conversion effi ciency of 10.60% and improved stability.